Deceiving Phenotypic Susceptibility Results on a Klebsiella pneumoniae Blood Isolate Carrying Plasmid-Mediated AmpC Gene blaDHA-1 - Realegeno, Susan; Ward, Kevin; Garner, Omai B.; Yang, Shangxin (Frontiers in Cellular and Infection Microbiology, 2021)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) frequently causes hospital-acquired infections and is associated with high morbidity and mortality. CRKP can have multiple resistance mechanisms and only a few can be routinely detected by commercial molecular or phenotypic assays making surveillance for CRKP particularly challenging. In this report, we identified and characterized an unusual non–carbapenemase-producing CRKP carrying a rare plasmid-borne inducible AmpC gene, blaDHA-1. The isolate was recovered from blood culture of a 67-year-old female presenting with sepsis post bladder surgery and ureteral stent removal. The primary isolate displayed an indeterminate susceptibility pattern for ceftriaxone by broth microdilution, but was susceptible by disk diffusion with one colony growing within the zone of inhibition. The ceftriaxone resistant colony was sub-cultured and had a minimum inhibitory concentration (MIC) of 2 ug/ml for imipenem (intermediate) and a zone size of 18 mm for ertapenem (resistant), but remained susceptible to cefepime and meropenem. Further phenotypic characterization of this sub-cultured isolate showed carbapenemase activity. Whole genome sequencing (WGS) revealed the presence of two subpopulations of a K. pneumoniae (MLST sequence type 11) from the primary blood culture isolate: one pan-susceptible to beta-lactams tested and the other resistant to the 3rd generation cephalosporins and ertapenem. WGS analysis identified the resistant K. pneumoniae harboring IncFIB(K) and IncR plasmids and the presence of plasmid-borne beta-lactam resistance genes blaOXA-1 and blaDHA-1, an inducible AmpC gene. Additional resistance genes against quinolones (aac(6′)-Ib-cr, oqxA, oqB), aminoglycoside (aph(3′)-Ia), sulfonamide (sul1), and tetracycline (tet(A)) were also identified. DHA-1 positive K. pneumoniae have been previously identified outside the US, particularly in Asia and Europe, but limited cases have been reported in the United States and may be underrecognized. Our study highlights the importance of using both extended phenotypic testing and WGS to identify emerging resistance mechanisms in clinical Enterobacterales isolates with unusual antimicrobial resistance patterns.